2001
DOI: 10.1021/es0105109
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbon and Particulate Emissions from Two-Stage Combustion of Polystyrene:  The Effect of the Primary Furnace Temperature

Abstract: A study is presented on laboratory-scale combustion of polystyrene (PS) to identify staged-combustion conditions that minimize emissions. Batch combustion of shredded PS was conducted in fixed beds placed in a bench-scale electrically heated horizontal muffle furnace. In most cases, combustion of the samples occurred by forming gaseous diffusion flames in atmospheric pressure air. The combustion effluent was mixed with additional air, and it was channeled to a second muffle furnace (afterburner) placed in seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
67
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 35 publications
(70 reference statements)
10
67
0
Order By: Relevance
“…Since polystyrene ((C 8 H 8 ) n ) also converts primarily to styrene (∼75%) [12], it may be considered as a surrogate for polystyrene combustion as well. Thus, this investigation also relates to past work in this laboratory on the combustion and emissions of waste polystyrene (PS), styrene, and ethylbenzene [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Combustion of polystyrene (PS), which amounts to 22 wt% of all high-volume waste plastics [29], generates larger amounts of polycyclic aromatic hydrocarbons (PAH) and soot than other plastics.…”
Section: Introductionmentioning
confidence: 88%
“…Since polystyrene ((C 8 H 8 ) n ) also converts primarily to styrene (∼75%) [12], it may be considered as a surrogate for polystyrene combustion as well. Thus, this investigation also relates to past work in this laboratory on the combustion and emissions of waste polystyrene (PS), styrene, and ethylbenzene [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Combustion of polystyrene (PS), which amounts to 22 wt% of all high-volume waste plastics [29], generates larger amounts of polycyclic aromatic hydrocarbons (PAH) and soot than other plastics.…”
Section: Introductionmentioning
confidence: 88%
“…Previous studies have demonstrated that PAHs could be generated from incineration of combustible materials in MSW such as plastics including HDPE, PP, PVC (Li et al 2001;Wheatley et al 1993;Müller et al 1997), PE (polyethylene) (Li et al 1995) and PS (polystyrene) (Wang et al 2001;Durlak et al 1998;Westblad et al 2002), rubber (Arion et al 2001), and biomass material (McGrath et al 2001) containing kitchen waste, bamboo, wood, straw, etc. In the classified MSW, significant decreases of plastics, metal and glass content were observed, while an increase of kitchen waste and biomass was also noted (Table 1).…”
Section: Factors Affecting Pahs In Residues From Msw Incinerationmentioning
confidence: 99%
“…Additionally studies were conducted to assess emissions from a range of burning materials under well-controlled conditions during small bench-scale experiments [26][27][28][29][30][31][32][33][34][35][36][37][38], emissions from largescale simulated room fires which were set up with a variety of furnishing materials [39][40][41][42] and emissions from vehicle fires [43]. These studies provide essential information on air pollutants released during combustion of materials.…”
Section: Introductionmentioning
confidence: 99%
“…The most extensively studied class of combustion products was inorganic gases. A small number of studies also investigated other pollutants including VOCs [27,31,32,35,39,44], PAHs [27][28][29]31,33,37,38,[45][46][47][48], dioxins and/or other persistent organic pollutants [33,40,47,[49][50][51][52] and particle size distribution [45,53]. Organic compounds were considered to be a potential hazard, but in most studies individual compounds have not been identified or quantified.…”
Section: Introductionmentioning
confidence: 99%